2013
DOI: 10.1111/hepr.12106
|View full text |Cite
|
Sign up to set email alerts
|

Side population in LX2 cells decreased by transforming growth factor‐β

Abstract: These results show that LX2 cells contain an SP fraction and that TGF-β signaling is involved in the induction of ECM deposition as well as the number of SP cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…In addition, TGF-β induces differentiation of quiescent hepatic stellate cells into activated cells in the liver (8), fibrosis through extracellular matrix (ECM) deposition and HCC (9). TGF-β binds several proteins, activates several signaling pathways and is involved in HCC progression (10).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TGF-β induces differentiation of quiescent hepatic stellate cells into activated cells in the liver (8), fibrosis through extracellular matrix (ECM) deposition and HCC (9). TGF-β binds several proteins, activates several signaling pathways and is involved in HCC progression (10).…”
Section: Introductionmentioning
confidence: 99%
“…Activated hepatic stellate cells (HSCs) are known to participate in ECM remodeling by producing various types of collagen, MMPs, TIMPs, and TGF-β1, thus deeply influencing fibrotic progression and regression (8,9). Numerous studies have indicated that the activation of HSCs is the cytological basis and the main initiator of hepatic fibrosis (10)(11)(12)(13). Consequently, the inhibition of HSC proliferation has become an important antifibrotic therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%